Translational PK–PD model for in vivo CAR‐T‐cell therapy delivered using CAR mRNA‐loaded polymeric nanoparticle vector - Se Jin Kim; Ganesh M. Mugundu; Aman P. Singh (Clinical and Translational Science)
Abstract Autologous chimeric antigen receptor (CAR) T‐cell therapy has demonstrated remarkable response rates, yet its widespread implementation is hindered by logistical, financial, and physical constraints. Additionally, challenges such as poor persistence and allorejection are associated with allogeneic cell therapies. An innovative approach involves in vivo transduction of endogenous T‐cells through the administration of CAR mRNA encapsulated in polymeric nanoparticles (NPs), resulting in transient CAR surface expression on circulating T‐cells. This method presents a promising alternative, although the dose–exposure–response relationship of in vivo CAR‐Ts remains poorly elucidated. The transient nature of CAR expression may necessitate repeated dosing, potentially introducing additional hurdles like cost and patient compliance. To address this issue, we have devised a translational pharmacokinetic–pharmacodynamic (PK–PD) model that characterizes the transient surface CAR expression following mRNA‐encapsulated NP administration, leveraging in vitro and in vivo data alongside critical binding kinetic parameters sourced from literature. Our model adequately captures the transient surface CAR expression in both settings, while incorporating known physiological parameter values and exhibiting precise estimation of unknown parameters (coefficient of variation < 30%). Global sensitivity analyses underscore the significance of intracellular mRNA stability, highlighting the sensitivity of parameters linked to free intracellular mRNA concentration. Model‐based simulations indicate that optimizing dose and dosing frequency can achieve sustained CAR expression, despite the transient protein expression characteristic of mRNA‐based therapies. This mechanistic PK–PD model holds potential for integration into physiologically‐based pharmacokinetic models, facilitating the translation of in vivo CAR‐T‐cell therapies from preclinical studies to human applications.